INFLUENCE OF MOTIVATION TOURIST AND TOURIST EXPERIENCE INTEREST TO TOURISTS VISIT BACK TO TOURISM IN WEST SUMATRA: SEEKING NOVELTY MEDIATION AS VARIABLE - Brama Kumbara, Vicky; M. Afuan; Ramdani Bayu Putra (Dinasti Publisher, 2020)
The development of tourist destinations today, has motivated research on revisit intention to be an important factor to be researched. This study seeks to examine the influence of tourist motivation and tourist experience on the revisit intention of tourists in West Sumatra which is mediated by the novelty seeking variable. The population of this research is tourists who visit tourist objects in West Sumatra. Samples were taken using accidental sampling method as many as 150 respondents. This study uses a Structural Equation Modeling (SEM) model with Smart PLS 3 as an analysis tool. The results of the analysis show that tourist motivation is the main factor that determines tourism revisit intention, while tourist experience and novelty seeking have no real role in increasing revisit intention. Another fact also finds that tourist motivation and tourist experience are the determining factors for novelty seeking. Whereas in another case novelty seeking as an intervening variable in this study was not proven to play a role in strengthening the influence of tourist motivation and tourist experience on revisit intention. In the future, these findings are expected to have implications for local governments in order to improve facilities or infrastructure and better deregulation of existing tourist destinations, so that all factors in this study can increase revisit intention